Entrepreneurship training and online marketplace participation among female persons with disabilities - Siew Wei Gan; Vengadeshvaran Sarma; Yu Hoe Tang; Siew Chen Sim (Asian Development Bank Institute (ADBI), 2022)
Online marketplace participation is a strategy for reducing barriers for female entrepreneurs who qualify as persons with disabilities (PWDs). Adapting a framework focused on causal interaction, entrepreneurial action, and the sociocultural context, we analyzed data using a mixed-methods approach from an entrepreneurial training program aimed at PWDs and implemented in three Southeast Asian nations, namely Indonesia, Malaysia, and the Philippines, to evaluate whether online marketplace participation helps female PWDs generate better income and support their families. Findings indicate that female PWD entrepreneurs who participate in the online marketplace generate better earnings than those who do not, although heterogeneities by nature of the product/service in question are prevalent. The results also show that trainees are better able to meet their families' financial needs. Despite the advantages, online marketplace participation among female PWD entrepreneurs is still low due to constraints regarding capital, technical know-how, and suitability of products. Hence, targeted intervention is necessary to enhance their participation.
Keywords: I31; L26; O17; 330; entrepreneurship; PWDs; online marketplace; training